2020
DOI: 10.3389/fbioe.2020.00754
|View full text |Cite
|
Sign up to set email alerts
|

Development of Natural-Based Bone Cement for a Controlled Doxorubicin-Drug Release

Abstract: Osteosarcoma (OS) accounts for 60% of all global bone cancer diagnoses. Intravenous administration of Doxorubicin Hydrochloride (DOXO) is the current form of OS treatment, however, systemic delivery has been linked to the onset of DOXO induced cardiomyopathy. Biomaterials including calcium phosphate cements (CPCs) and nanoparticles (NPs) have been tested as localized drug delivery scaffolds for OS cells. However, the tumor microenvironment is critical in cancer progression, with mesenchymal stem cells (MSCs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Besides the possibility to directly integrate active molecules into 3D frameworks, therapeutic agents can also be loaded into scaffolds or hydrogels upon previous encapsulation into ad hoc designed nano- or micro-carriers, such as polymeric or inorganic particles [ 22 , 23 ]. This approach has the advantage of protecting the payload from fast degradation/deactivation and enhances control over its release kinetics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the possibility to directly integrate active molecules into 3D frameworks, therapeutic agents can also be loaded into scaffolds or hydrogels upon previous encapsulation into ad hoc designed nano- or micro-carriers, such as polymeric or inorganic particles [ 22 , 23 ]. This approach has the advantage of protecting the payload from fast degradation/deactivation and enhances control over its release kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…In the same year, Ferreira et al demonstrated the possibility to incorporate similar polymeric particles into PLA scaffolds fabricated via thermally induced phase separation with the aim to develop biomimetic constructs for wound healing and soft tissue regeneration [ 32 ]. Very recently, PLGA particles encapsulating doxorubicin hydrochloride were added to a calcium phosphate bone cement, resulting in a more effective and localized delivery of the cargo compared to direct drug loading into the cement as such [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the porosity of CPCs is in the range of 30–55% and is dependent on the liquid/powder ratio: higher ratios are related to an increase in porosity and vice versa [ 71 ]. Furthermore, the presence of a specific level of porosity makes this product also an excellent carrier for a controlled drug delivery system [ 72 , 73 , 74 ]. In this respect, the porosity of CPCs can be enhanced through the introduction of solid porogens, such as inorganic substances and polymers, or by the use of foaming agents [ 75 ].…”
Section: Chemically Consolidated Calcium Phosphates As 3d Injectable Scaffoldsmentioning
confidence: 99%
“…Among the various modes of hyperthermia, magnetic hyperthermia is an exciting modality to kill cancer cells selectively by applying an external time varying magnetic field using a magnetic specimen as a hyperthermia agent. Magnetic hyperthermia can be accomplished via magnetic thermoseed or selective internalization of magnetic nanoparticles within cells as an invasive or noninvasive approach. However, thermoseed may be a suitable approach for bone cancer treatment as the bone fillers or substitute material employed can be made both magnetic hyperthermia and chemotherapeutic agents by combining magnetic nanoparticles and appropriate drugs along with the filler materials. Furthermore, unlike the other modes of hyperthermia treatment for cancers, in the local magnetic hyperthermia where the thermoseed is placed and removed surgically before and after treatment, in the case of bone cancer treatment, there is no need for a second surgery to remove the thermoseed as it acts as a bone filler material or tissue engineering scaffold. , …”
Section: Introductionmentioning
confidence: 99%